Gut Microbiomics—A Solution to Unloose the Gordian Knot of Biological Effects of Ionizing Radiation. (6th July 2017) - Zhang, Amy; Steen, Tomoko Y
Abstract: The Chernobyl and Fukushima nuclear accidents have called forth a growing body of research on their biological aftermaths. A variety of wild organisms, including primates, birds, fish, insects, and worms are being studied in the affected areas, with emerging morphological, physiological, and genetic aberrations ascribed to ionizing radiation. Despite the effort in surveying Chernobyl and Fukushima wildlife, little is known about the microorganisms associated with these radiation-contaminated animals. The microbiota, especially the gut commensal, plays an important role in shaping the metabolic reservoir and immune system of the host, and is sensitive to a wide array of environmental factors, including ionizing radiation. Humans and limited numbers of laboratory species have been the main subjects of microbiome studies, however, a more practical insight on host–gut microbiota dynamics under environmental impact should be explored in natural habitats. In this analysis, we introduced a working model explaining possible mechanisms of ionizing radiation on the gut microbiota, with an evaluation of the gut microbiota as a potential biomarker for exposure to ionizing radiation.